Protest Against Natural Destruction Reflected in Elizabeth Rudnick's The Curse Of Maleficent Novel (2014): A Sociological Approach - Purnamasari, May; , Dr. M. Thoyibi, M.S (2016)
May Purnamasari. A320120204. PROTEST AGAINST NATURAL DESTRUCTION REFLECTED IN ELIZABETH RUDNICK'S THE CURSE OF MALEFICENT NOVEL (2014): A SOCIOLOGICAL APPROACH. Research Paper. Department of English Education. School of Teacher Training and Education. Muhammadiyah University of Surakarta. This study is about natural destruction done by humans which is reflected in The Curse of Maleficent novel (2014) written by Elizabeth Rudnick, and it is analyzed by using a sociological approach. The purpose of this research is to describe the indicator of natural destruction, to explain the cause of natural destruction, to explain the impact of natural destruction, to describe how natural destruction is depicted in the novel, and to reveal why the author addresses natural destruction in her novel. This research is a qualitative research. The primary data of this research is The Curse of Maleficent novel (2014) which is written by Elizabeth Rudnick. The secondary data of this research are website, author's biography, articles and several books related to this research. There are four conclusions in this research. First, there are two indicators of natural destruction, namely pollution and destruction of forest. Second, the cause of natural destruction is human activity that can harm environment. Third, the impacts of natural destruction are illness and death. Fourth, there are fives things that support the story of natural destruction of the novel, namely the Human world, the Moors, war, human greed, and harmony. Fifth, Elizabeth Rudnick raises the issue of natural destruction in her novel to reveal about natural destruction that has occurred in environment.